In situ vanadophosphomolybdate impregnated into conducting polypyrrole for supercapacitor. (20th December 2020) - Vannathan, Anjana Anandan; Maity, Sukanya; Kella, Tatinaidu; Shee, Debaprasad; Das, Partha Pratim; Mal, Sib Sankar
Abstract: The fast modernization and advancement in lifestyle increase the consumption of power daily due to all innovative technologies, e.g., hybrid vehicles, solar cells, smart power grid, communication devices, artificial hearts, etc. Conducting organic polymer-based energy storage devices had attracted much attention due to the conductive nature for a long time. However, its application has been restricted because of swelling and shrinking capability during the charge and discharge cycle. The combination of redox-active inorganic metal oxides, such as polyoxometalates (multi-metal oxide cluster) with conduction polymers, could enhance the material's stability due to its fast multi-electron redox property. Here, we report the two polypyrroles combined vanadophosphomolybdates, namely PPy-H4 [PVMo11 O40 ] and PPy-H5 [PV2 Mo10 O40 ] nanohybrid electrode materials. The PPy-H5 [PV2 Mo10 O40 ] electrode material behaves as pseudocapacitance and can deliver an excellent capacitance of 561.1 F/g in 0.1 M H2 SO4 electrolyte solution at a 0.2 A/g current density, indicating capacitive composite material. The electrochemical impedance spectroscopy (EIS) reveals that PPy-H5 [PV2 Mo10 O40 ] is more capacitive than PPy-H4 [PVMo11 O40 ] and PPy with equivalent series resistance (ESR) of 5.74 Ω. The cell capacitance of PPy-H5 [PV2 Mo10 O40 ] and PPy-H4 [PVMo11 O40 ] are found to be 5.38 and 9.15 mF, stipulating in small SC cell application. Likewise, the PPy-H5 [PV2 Mo10 O40 ] nanohybrid electrode shows better responsive behavior with a relaxation time of 0.16 ms. Furthermore, the PPy-H5 [PV2 Mo10 O40 ] electrode exhibits outstanding cycle stability, retaining ~95% of its capacitance after 4500 cycles as compare to PPy-H4 [PVMo11 O40 ] (~91%) electrode. Graphical abstract: Image, graphical abstract